Study on morphology and electrical properties of graphene oxide decorated with nickel oxide for electrochemical sensor / Misliana Md Taib - Misliana, Md Taib (2019)
In this work, graphene oxide (GO) and graphene oxide decorated with nickel oxide (GO-NiO) were synthesized by using modified Hummer’s method and hydrothermal method respectively. The synthesized nanoparticles were subjected to morphology and electrical testing. The EDS data shows oxygen, carbon and nickel elements present in the synthesized product. The FESEM images of GO shows the nanoparticles is in flakes form whereby the FESEM images for graphene oxide decorated with nickel oxide in oval-flakes form. Impedance Spectroscopy (IS) were used to study an electrical properties of synthesized product. Later, the result were discussed using Nyquist graph to confirm the conductivity of the GO and GO-NiO with presence of semicircle and 45° straight line. Since GO-NiO consists elements of GO and NiO, it has the ability to conduct an electricity. As a conclusion, it was observed that there is significant different in the reading of conductivity with an addition of NiO into GO.